Panel II: Presidential Lawmaking Powers: Vetoes, Line Item Vetoes, Signing Statements, Executive Orders, and Delegations of Rulemaking Authority - David Schoenbrod; Frank Easterbrook; Steven Ross; Theodore Olson (Washington University Law Quarterly, 1990)
My topic is the delegation of legislative power which occurs when a statute authorizes the Executive to make the rules of conduct. My purpose is to urge you to begin to rethink whether this prevalent practice is a wise and good thing.